2023
DOI: 10.1038/s41467-023-35953-y
|View full text |Cite
|
Sign up to set email alerts
|

Magmatic plumbing and dynamic evolution of the 2021 La Palma eruption

Abstract: The 2021 volcanic eruption at La Palma, Canary Islands, was the island’s most voluminous historical eruption. Little is known about this volcano’s feeding system. During the eruption, seismicity was distributed in two clusters at ~10-14 km and ~33-39 km depth, separated by an aseismic zone. This gap coincides with the location of weak seismic swarms in 2017-2021 and where petrological data have implied pre-eruptive magma storage. Here we use seismological methods to understand the seismic response to magma tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 57 publications
(97 reference statements)
8
31
0
Order By: Relevance
“…During the period we ob-served the occurrence of the fracture set, also shallower earthquakes were identified. In fact, a comparison to available seismic catalogues [del Fresno et al 2023] * reveals a chronologic succession, with large earthquakes at the deeper reservoirs at 34 and 12 km depths, followed in the end of November 2021 and early December 2021 by more shallow earthquakes at <12 km depth, which is followed by the new eccentric crater on the northern flank of the main eruptive crater and then by the divergent fracture on the southern side as described in our work. In this view, the vertical time lag between earthquake and eruption changes is less than one day, whereas the horizontal time lag between the northern vent and the fracture emergence in the south is up to four days.…”
Section: Importance Of Graben For the 2021 Cumbre Vieja Eruptionsupporting
confidence: 70%
“…During the period we ob-served the occurrence of the fracture set, also shallower earthquakes were identified. In fact, a comparison to available seismic catalogues [del Fresno et al 2023] * reveals a chronologic succession, with large earthquakes at the deeper reservoirs at 34 and 12 km depths, followed in the end of November 2021 and early December 2021 by more shallow earthquakes at <12 km depth, which is followed by the new eccentric crater on the northern flank of the main eruptive crater and then by the divergent fracture on the southern side as described in our work. In this view, the vertical time lag between earthquake and eruption changes is less than one day, whereas the horizontal time lag between the northern vent and the fracture emergence in the south is up to four days.…”
Section: Importance Of Graben For the 2021 Cumbre Vieja Eruptionsupporting
confidence: 70%
“…Possible implications for magma propagation and future eruptions based on our volume growth rate can be inferred from Galetto et al (2022), who found that magma volume increase in crustal reservoirs at rates <0.01 km 3 /yr have not led to magma propagation in 90% of cases. The magma supply episodes analyzed by Galetto et al (2022) were located in the middle-to-upper crust, so in the RHM case the eruption likelihood would be lower, but still deserves attention, as magma may ascend relatively swiftly from large depths (e.g., Mayotte and Cumbre Vieja, La Palma, eruptions; Cesca et al, 2020;del Fresno et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The magma supply episodes analyzed by Galetto et al. (2022) were located in the middle‐to‐upper crust, so in the RHM case the eruption likelihood would be lower, but still deserves attention, as magma may ascend relatively swiftly from large depths (e.g., Mayotte and Cumbre Vieja, La Palma, eruptions; Cesca et al., 2020; del Fresno et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…We consider that this area is affected by partial melting due to the very low Vs values. Even if the RF method we used in this work lacks sufficient spatial resolution, previous seismological studies (D'Auria et al, 2022;Del Fresno et al, 2023) demonstrated the presence of at least two magmatic chambers located within the LVZ. This finding is corroborated by petrological (Klügel et al, 2000(Klügel et al, , 2005 and gravimetric studies (Montesinos et al, 2023 postulated that the precursory seismicity recorded between 2017 and 2021 indicated that the subcrustal chamber was fed, through repeated magmatic transfer episodes, by the lower magmatic chamber, located at about 25 km depth (represented by a solid ellipse in Figure 3).…”
Section: Interpretation Of the Geological Modelmentioning
confidence: 96%